Non-fatal Overdose with U-47700: Identification in Biological Matrices - Vogliardi, Susanna; Stocchero, Giulia; Maietti, Sergio; Tucci, Marianna; Nalesso, Alessandro; Snenghi, Rossella; Favretto, Donata (Current Pharmaceutical Biotechnology, 2018)
Background/Objective: We report on a case of severe intoxication after insufflation of U-47700, a synthetic opioid that acts as a selective agonist of the μ-opioid receptor, and is several times more potent than morphine. A man in his 30s was found irresponsive in his apartment and was brought to the emergency department of a local hospital. A comatose state and severe respiratory depression were present. Hetero anamnesis revealed that the patient could have taken the substance named “U-47700”, bought on the Internet. After supportive care, the patient fully recovered. Method: Urine, blood and a white powder found at his home were collected during his hospital stay and sent for testing using liquid chromatography-high resolution mass spectrometry (LC-HRMS) on an Orbitrap instrument. Later, his pubic hair was also collected. A standard comprehensive toxicology screening was performed. Results: U-47700 was identified in all biological samples and in the seized white powder. Using liquid chromatography-high resolution mass spectrometry (LC-HRMS) the presence of U-47700 and its phase I and phase II metabolites in blood, urine and pubic hair was confirmed. U-47700 was determined at 94 ng/mL and 5.2 ng/mL in blood at the admission and the day after, respectively, and 3.02 ng/mg in pubic hair, together with its metabolites. No other opioid nor designer drug could be detected in blood and urine, while in pubic hair Cocaine, Benzoylecgonine, Norcocaine, Mephedrone, Ketamine, Norketamine, 3,4-Methylenedioxymethamphetamine, Tetrahydrocannabinol and Cannabinol were also detected. Conclusion: The toxicological findings confirmed the use of U-47700 in the intoxicated patient and also revealed a history of a poly-drug use. The use of LC-HRMS allowed the easy identification of the NPS and its metabolites in fluids and hair.
Keywords: synthetic opioid